2009
DOI: 10.18433/j3zw2c
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and Study Conditions for the Determination of Bioequivalence of Highly Variable Drugs

Abstract: -Purpose. The FDA Working Group on Highly Variable (HV) Drugs recently presented procedures and conditions for determining the bioequivalence (BE) of HV drug products. They included analysis by the method of scaled average BE (SABE), a switching coefficient of variation of CV S = 30% and a regulatory standardized variation of CV 0 = 25% for applying SABE, and the use of a secondary regulatory criterion restricting to 0.80-1.25 the point estimate for the ratio of the estimated geometric means (GMR) of the two f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 19 publications
4
28
0
Order By: Relevance
“…But as reported earlier, this method has a higher than 5% consumer risk (27). This observation was confirmed (28,29).…”
Section: Other Commentssupporting
confidence: 80%
“…But as reported earlier, this method has a higher than 5% consumer risk (27). This observation was confirmed (28,29).…”
Section: Other Commentssupporting
confidence: 80%
“…As it is possible that, using RSABE, two products can be shown to be bioequivalent but have an estimated GMR outside of the 0.8 to 1.25 range, it is thought that use of the secondary point estimate constraint will improve the confidence of clinicians and patients (15,28). Several simulation studies investigating the relationship between FDA's recommended RSABE approach and study power have shown that, when within-subject variability exceeds 50-60%, the point estimate constraint becomes the dominant regulatory criterion rather than the scaling (43)(44)(45). It has also been shown that applying the point estimate constraint can increase the sample size needed to show BE for drugs with within-subject variability >50-60% (45).…”
Section: Fda Recommendations For Designing Rsabe Studiesmentioning
confidence: 99%
“…The FDA sets σ W0 at 0.25, but also proposes an implementation algorithm that does not permit BE limits to scale until the observed within-subject variability reaches the cutoff value of 0.294 for s WR . Endrenyi and Tothfalusi (44) argue that the FDA's approach to RSABE is discontinuous and conducted simulations claiming that, when σ W0 ranges from 0.246 to 0.294, consumer risk is substantially larger than 5% and the regulatory uncertainty about a decision on acceptance or rejection is enhanced. This claim is based on a different definition of consumer risk than FDA uses.…”
Section: Controversiesmentioning
confidence: 99%
“…This has been done in order to have a smooth transition between scaling and no scaling, and to avoid an excessive consumer risk at intra-subject variability slightly higher than 30%, which are very frequent (31). In contrast, the US-FDA employs a proportionality constant that is more permissive (wider limits) and there is a lack of consistency between the CV that corresponds to that constant and the CV where scaling starts to be acceptable (CV= 30%), which increases the consumer risk.…”
Section: Highly Variable Drug Productsmentioning
confidence: 99%